Curva de retenção de água do solo em Cerrado no norte do Pantanal Mato-Grossense no período seco - Massad, Heloisa Agnes Bodnar (2018)
The soil water retention curve (SWRC) presents several practical, technical and scientific applications, such as: determination of soil field capacity, permanent wilting point, available water for the plants. The study was carried out in the northern Mato Grosso Pantanal, in a predominant acuri palm region, during the dry season of 2017, under different treatments of soil cover (addition litter "CS", removed litter "RT" and control area "CT"). Soil physical variables (soil density and soil moisture) were analyzed following recommended procedures in the literature. For the estimation of the unsaturated hydraulic conductivity of the soil, the strain infiltrator method was used. SWRC was performed through the tension table, the Richards chamber and the automated method. The results of unsaturated soil conductivity showed that the control treatment had the highest values, however there were significant differences between the treatments in this study. CRAS, with differences in organic matter content between treatments, presented a difference between treatments. The soil water content in the FC (Field Capacity) and in the PWP (Permanent Wilting Point) reached its maximum value, 0.38 m³ m-3 and 0.21 m³ m-3 , respectively, in the treatment that had the (CS), corroborating with values described in the literature and with significant differences between treatments. From this it is concluded that the different treatments of the soil cover for the studied region, in the dry period, presented significant differences for the variables.